A High-Power Microwave Reflectarray Antenna Based on Perforated Dielectric Substrate - Abdi Tazehabadi, S.; Jam, S. (Advanced Electromagnetics, 2019)
A high power microwave antenna based on the reflectarray concept is designed and investigated in this paper. The reflectarray aperture is directly driven by an azimuthally symmetric mode and a directional boresight beam is realized through azimuthally introducing a phase shift of 90 to the phase shift profile of reflectarray unit cells. A sample model operating at X-band is designed to verify the validity of the proposed approach. Variable diameter air-filled holes through a host dielectric material are exploited as the phase-shifting unit cells because of the advantage of higher power handling capacity. Theoretical analysis and full-wave simulations are accomplished and results are in good agreements. A collimated beam of circular polarization with peak gain of 20.2 dB and axial ratio of 1.3 are achieved at the boresight direction for the design frequency of 10 GHz. The radiation performance of the proposed antenna as well as its compact structure makes it a potential candidate for high gain high power applications.